Excessive iodine status among school‐aged children in the State of Qatar: Results of the National Iodine Deficiency Disorder Survey - Mohamed Hamad J. T. Al‐Thani; Salah Abdulla Sh. A. Alyafei; Kholoud Ateeq K. M. Al‐Motawaa; Shamseldin Ali Khalifa; Syed Hassan Bin Usman Shah; Benjamin Vinodson; Sureshbabu Kokku; Amit Mishra (Wiley, 2023)
Abstract Background Iodine deficiency poses a significant public health challenge worldwide, particularly in preschool children and pregnant women. Assessing the iodine intake at a population level is essential, as both deficient and excessive iodine status can have adverse health consequences. The main objective of this survey is to understand the iodine deficiency status in schoolchildren aged 6-12 years in the State of Qatar. Methods A cross‐sectional survey was conducted from March to June 2014 among school‐aged children using a two‐stage cluster sampling technique. Anthropometric, biochemical, clinical, and dietary parameters for seafood were collected. Spot urine samples were collected from 967 participants, and a repeat random subsample urine was collected from 288 participants. Overall median urinary iodine concentration (UIC) was calculated. Iodine content in household salt samples was estimated by qualitative and quantitative methods. Mann-Whitney U test was used for comparison. Results The median UIC was 333.2 μg/L (IQR = 228.6). UIC prevalence rates between 300-999 and >1000 μg/L were 56.7% and 2.8%, respectively. The goiter prevalence was 0.4%. A significant difference was noted in overall median UIC levels between boys and girls (p = 0.003). Adequate iodized salt consumption was reported by 74.9% of households, and weekly seafood consumption was reported by one third of the respondents. Conclusion The results indicate an excess intake of iodine among the studied population in the State of Qatar, and national efforts are needed to bring iodine intake and concentration levels within the cutoff value for the concerned survey population's age group. In addition, a surveillance system needs to be set up for continuous monitoring of iodine content and salt intake at the population level in the State of Qatar.